Domestic political constraints to foreign aid effectiveness - Lisa Montanari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
The Aid Effectiveness Literature has recently investigated the effects of foreign aid on economic growth through country policies. Different results have been reached across different studies mainly due to their sensitivity to policy measures and data samples. The internal political setting of LDCs may influence the effect of aid over policy distortions and represent a rea- son for this ambiguity. I present a model in which the government has complete control over the policy implementation. The interaction with a domestic special interest group which benefits from distortions and a benevolent donor agency affects its decisions. I show that, while the government is always better off when foreign aid is present, the economy may be characterized by a more or less distorted equilibrium depending on the way aid modifies the policy effect on economic welfare. When aid is more effective (it reduces the negative effect of the distortion on welfare) the government has an incentive to pursue higher levels of distortion in order to extract a larger contribution from the lobby. Aid and the policy distortion become substitutes in the governments utility. Hence the distortion in equilibrium is larger than the "natural" level it would occur in the absence of aid. In such a case, the ability of the lobby to extract gains from aid non trivially leads to a less distorted equilibrium. The same result generally yields when aid is conditional on the policy implemented. Anyway I show that the possibility for more-distorted equilibria to arise does not completely disappear. When the "natural" distortion of the economy is large, a benevolent donor might still have an incentive in not properly addressing conditionality issues.
Keywords: 330